Fully coupled segregation and precipitation kinetics model with ab initio input for the Fe-Au system. (1st January 2023) - Scheiber, D.; Svoboda, J.; Fischer, F.D.; Böhm, H.J.; Romaner, L.
Abstract: For designing new and improved materials, predictive modeling of precipitation and segregation kinetics is required. So far, no modeling approach is available that couples precipitation with ab initio segregation data. We derive the mathematical basis for a model to describe segregation and precipitation kinetics with grain boundary segregation energies obtained from ab initio simulations. The model is implemented rigorously and validated with experimental data on a Fe-Au system from literature. Graphical abstract: Image, graphical abstract